Is Default Risk Related to Inflation? - Abdelaziz Chazi (Journal of Accounting, Business and Management (JABM), 2007)
I use tests such as Vector Autoregression estimates, Granger causality, and Impulse response function to show that inflation is a statistically significant predictor of expected default risk or credit quality. Credit quality, measured by Moodys total net downgrade change, by quarter, from 1990 to the second quarter of 2000, is used as a proxy for default risk. This sample period is characterized by a first couple of years of recession followed by a longer period of economic expansion. The net downgrade change in Moodys corporate bonds rating, at the aggregate level, and hence the net default risk for all investors, is more likely to increase with one-quarter-lag increase in inflation.